Penerapan Model Pembelajaran Kooperatif Tipe Scramble Dalam Meningkatkan Hasil Belajar Peserta Didik Kelas X SMAS Mutiara Bangsa - Mahyudin, Haryati (Peneliti.net, 2023)
This research is a pre-experimental research using a Pre-test and Post-test Group design involving the dependent variable, namely Physics learning outcomes and the independent variable, namely the scramble type cooperative learning model. The population in this study were all students in class X MIA SMAS Mutiara Bangsa South Halmahera with a sample of 20 students. The research instrument used was the Physics learning outcomes test. The results of the descriptive analysis show that the average value of Physics learning outcomes for class 13.92 and a standard deviation of 2.37 with an average Normalized Gain value of 0.54 in the medium category. From the results of the analysis it can be concluded that the scramble type cooperative learning model can improve the physics learning outcomes of class X MIA SMAS Mutiara Bangsa South Halmahera students.